2020
DOI: 10.1017/s1537592719005000
|View full text |Cite
|
Sign up to set email alerts
|

Demography and the Future of Democracy

Abstract: The world is in the midst of a demographic recession. This counters what should be a long-term trend toward greater democracy. Recent research has shown that progress toward stable democracy is strongly associated with progress in the demographic transition. Since most of the world is rapidly dropping in fertility as more countries complete this transition, democracy should be spreading. However, a resurgence of anxiety, nationalism, and support for strong-man governance is associated with sudden waves of immi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Throughout, the Leave campaign wrongly claimed that the "United Kingdom sends £350 million to the European Union every single week." 6 The correct figure is £181 million, amounting to 1.2 percent of overall UK government spending. 7 The campaign suggested that the United Kingdom's contribution to the EU budget could be used to support the National Health Service (NHS), which faced pressures that the campaign in turn blamed on immigration.…”
Section: A Uk Politics the European Union And The Eu Referendummentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout, the Leave campaign wrongly claimed that the "United Kingdom sends £350 million to the European Union every single week." 6 The correct figure is £181 million, amounting to 1.2 percent of overall UK government spending. 7 The campaign suggested that the United Kingdom's contribution to the EU budget could be used to support the National Health Service (NHS), which faced pressures that the campaign in turn blamed on immigration.…”
Section: A Uk Politics the European Union And The Eu Referendummentioning
confidence: 99%
“…The Guardian, "Cameron Did Not Think EU Referendum Would Happen," https://goo.gl/Vsmgnt, accessed March 3, 2019 6. The following in-line quotes are from advertisements run by the Vote Leave campaign.…”
mentioning
confidence: 99%
“…Population aging, known as an age structure where there is an increasing proportion of dependent elderly and a decreasing number of descendants, has become the feature of developed countries in the past decades. The phenomenon requires state policies to manage the problems arising from the transition from different age structures, especially dramatic fiscal reforms to maintain welfare regimes sustainability (Cincotta, 2017 ; Goldstone & Diamond, 2020 , 869). The structural and institutional changes that widened economic inequality further put pressure on the state to provide welfare measures to lift living standards for those in need.…”
Section: Population Aging Rising Inequality and The Demand For Equal ...mentioning
confidence: 99%
“…A 2015 study found that 19 of the 33 most water-stressed countries by 2040 will be in the Middle East and North Africa (Maddocks, Young, and Reig 2015). Just as the Syrian drought of 2007-09 helped to create the conditions (such as displacement of rural populations, and rising food prices) for a meltdown of the political order in 2011, so future droughts will destabilize political orders in the region (Goldstone and Diamond 2020).…”
Section: Prospects For Political Reform In the Arab Worldmentioning
confidence: 99%